PENGEMBANGAN MODUL BAGI SISWA TEKNIK KOMPUTER JARINGAN PADA MATA PELAJARAN PEMROGRAMAN DASAR - Rengga Nofrianti; Muhammad Anwar Anwar (Universitas Negeri Padang, 2019)
This study explains how the learning module is developed on basic programming of Computer Network Engineering students. This study aims to determine the validity, practicality, and effectiveness of the basic programming module of Computer Network Engineering class X at SMK N 5 developed by problem solving strategy. This study is Research and Development (R & D) research by 4D modul implementation. The Development of instructional module using ADDIE model which consist of five stages such as Analysis, Design, Development, Implementation and Evaluation. There were three instruments that is used to collect the data in this research like validity questionnaire, practicality questionnaire and and effectiveness sheets. Based on the result carried out, this research has shown that the score for module validity from expert of learning material development is 0,82 and expert of learning media development is 0,77. Then for practicality, based on teacher responses the average score of 87% and 88% for students responses. So instead, it can be concluded that the module on basic programming is effective based on the average scores of experimental class that it was 80, compared by the average score of control class of 72. Keywords: Module, Basic Programming, Research and Development, ADDIE.